PLANTS AS NATURAL DYES ON SILK THREADS - Hasnawati Hasnawati (Universitas Negeri Makassar, 2021)
This research aims to: 1) identify what plants can be used as natural dyes on Makassar Bugis silk threads, 2) describe the process of staining Makassar Bugis silk threads using natural dyes, The object of the study is a natural dye on silk threads. This research is designed as case research with a qualitative descriptive approach. Data retrieval is done by observation, documentation, and trial. The data collection instruments used are observation guides and cameras. Data is analyzed qualitatively descriptively. The results of the study are known that: 1) plants that are used as producers of natural dyes are betel leaves, seppang wood, girlfriend leaves or pacci (korontigi), noni root, macang mango leaves (kuweni), pomegranate peel, and wet turmeric. 2) The process of making natural dyes on silk threads is starting from choosing plant parts that will be tested, drying, slicing, or cutting into small pieces, squeezing, mashing, cooking/boiling, to soaking the thread in a solution that has been made. Next washed thoroughly with cold water and dried in a shady place.